Metabolic profile and underlying antioxidant improvement of Ziziphi Spinosae Folium by human intestinal bacteria. (1st August 2020) - Yan, Yan; Fu, Cai; Cui, Xiaofang; Pei, Xiangping; Li, Aiping; Qin, Xuemei; Du, Chenhui; Du, Huizhi
Highlights: A method for the determination of compounds in fermented LZJSF is developed. Metabolic processes of LZJSF by human intestinal bacteria are profiled. LZJSF is metabolized to aglycones at 4 and 6 h and to phenolic acid at longer time. Metabolites shows better antioxidant effects at 4 and 6 h than at other times. LZJSF is expected to be a functional food to improve human health. Abstract: Ziziphi Spinosae Folium, the leaf of Ziziphus jujuba Mill. Var . spinosa ( Bunge ) Hu ex H. F. Chou (LZJS), is currently used as a healthy tea in China. This study evaluated the chemical components and antioxidant activities of LZJS flavonoid (LZJSF) and fermented LZJSF (FLZJSF) using human intestinal bacteria (HIB) through dynamic fermentation. Eighteen flavonoids were simultaneously identified in LZJSF using UHPLC-Q-Orbitrap-MS method, nine of which were targeted for a HIB metabolism study. Seven small phenolic acids were identified in FLZJSF. Not only at chemical level but also at PC12 cell level, FLZJSF samples fermented for 4 and 6 h showed significant positive correlation between their activities and flavonoid aglycones, which were transformed from LZJSF. However, FLZJSF samples (8 h and longer time) mainly contained phenolic acids and indicated weak activities. Thus, LZJSF was found to result in increased antioxidant activity and could be commercially utilized as a novel functional food.